Educational Impact of #IDJClub, a Twitter-Based Infectious Diseases Journal Club. (15th May 2022) - Schwartz, Ilan S; McCarty, Todd; Woc-Colburn, Laila E; Titanji, Boghuma K; Cutrell, James B; Cortes-Penfield, Nicolas W
Abstract: Background: Journal clubs have been an enduring mainstay of medical education, and hosting these on social media platforms can expand accessibility and engagement. We describe the creation and impact of #IDJClub, an infectious diseases (ID) Twitter journal club. Methods: We launched #IDJClub in October 2019. Using the account @IDJClub, an ID physician leads a 1-hour open-access Twitter discussion of a recent publication. All participants use the hashtag #IDJClub. Sessions started monthly, but increased due to demand during the coronavirus disease 2019 (COVID-19) pandemic. We used Symplur 's Healthcare Hashtag project to track engagement of #IDJClub per 60-minute discussion plus the following 30 minutes to capture ongoing conversations. We also conducted an online anonymous survey using Likert scales and open-ended questions to assess educational impact. Results: In its first 20 months, 31 journal clubs were held, with medians of 42 (interquartile range [IQR], 28.5–60) participants and 312 (IQR, 205–427.5) tweets per session. 134 participants completed the survey, of whom 39% were ID physicians, 19% pharmacists, 13% ID fellows, and 10% medical residents. Most agreed or strongly agreed that #IDJClub provided clinically useful knowledge (95%), increased personal confidence in independent literature appraisal (72%), and was more educational than traditional journal clubs (72%). The format addressed several barriers to traditional journal club participation such as lack of access, subject experts, and time. Conclusions: #IDJClub is an effective virtual journal club, providing an engaging, open-access tool for critical literature appraisal that overcomes several barriers to traditional journal club participations while fostering connectedness within the global ID community.